Application of computational intelligence methods in modelling river flow prediction: A review - Zaini N.; Malek M.A.; Yusoff M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Arts computing; Decision making; Evolutionary algorithms; Forecasting; Fuzzy neural networks; Intelligent computing; Neural networks; Rain; Rivers; Stream flow; Support vector machines; Computational intelligence methods; Computational intelligence techniques; Computational results; Hydrological cycles; Neural networks , fuzzy logic; Prediction accuracy; River flow models; River flow prediction; Fuzzy logic